Effects of natural and chemical stressors on Enchytraeus albidus: Can oxidative stress parameters be used as fast screening tools for the assessment of different stress impacts in soils? - Howcroft, C. F.
Enchytraeids are important organisms of the soil biocenosis. They improve the soil pore structure and the degradation of organic matter. These organisms are used in standardized testing, using survival and reproduction (6 weeks) as endpoints. The use of biomarkers, linked to ecologically relevant alterations at higher levels of biological organization, is a promising tool for Environmental Risk Assessment Here, enchytraeids were exposed for different time periods (two days and three weeks) to different soils (OECD artificial soil, different compositions in its organic matter, clay or pH value, and LUFA 2.2 natural soil) and different chemicals (Phenmedipham and copper). The main question addressed in the present study was if the effects of chemicals and different soil properties are preceded by alterations at the sub-cellular level, and if these endpoints may be used reliantly as faster screening tools for the assessment of different stress conditions in soils. The parameters measured in E. albidus whole body were: lipid peroxidation (LPO), total glutathione (TG), as well as the enzymatic activities of superoxide dismutase (SOD), catalase (CAT), glutathione reductase (GR), glutathione peroxidase (GPx) and glutathione S-transferase (GST). The results showed that biomarker responses in E. albidus were significantly affected by the soil type (GST CAT, GPx, GR and LPO) and the duration of exposure in OECD artificial soil (GST, GPx, GR, CAT and LPO) but not in LUFA 2.2 natural soil. For the abiotic factors studied, after 2 days, low pH decreased significantly the TG levels and the activities of CAT and GR,and low OM also significantly decreased CAT and GR activities. After 3 weeks, differences in soil properties caused a decrease in GR and GPx activities, whereas increased M activity was observed due to low organic matter and pH. Copper significantly increased the activities of CAT, GPx and GR, and decreased the activity of GST after 2 days as well as inscreasing LPO levels after 3 weeks. Phenmedipham increased LPO levels, associated with increased levels of TG as well as increased activities of CAT and GPx and decreased GST activity after 3 weeks exposure. This study shows that both abiotic and chemical stresses could be followed through biomarker analysis and that some of these determinations are potential endpoints in a quick soil contamination assessment procedure. (C) 2008 Elsevier Ltd. All rights reserved.